The Roman Empire : a very short introduction - Kelly, Christopher, 1964- (Very short introductions., 2006)
The Roman Empire was a remarkable achievement. This introduction covers the history of the empire at its height, looking at its people, religions and social structures. It explains how it deployed violence, 'romanisation', and tactical power to develop an astonishingly uniform culture from Rome to its furthest outreaches.